Characterization and sulfated modification of an exopolysaccharide from Lactobacillus plantarum ZDY2013 and its biological activities. (20th November 2016) - Zhang, Zhihong; Liu, Zhengqi; Tao, Xueying; Wei, Hua
Highlights: Only one exopolysaccharide fraction was obtained by HPSEC. Monosaccharide composition of EPS is simple which distinguishes with other L. plantarum EPS. Sulfated EPS displayed stronger radicals scavenging activities than EPS. Sulfated EPS could protect Caco-2 cells from damage induced by enterotoxin of Bacillus cereus . Abstract: An exopolysaccharide (EPS) from probiotics Lactobacillus plantarum ZDY2013 was purified to illustrate its molecular weight, monosaccharide composition and biological activities. The yield of EPS (429.4 ± 30.3 mg/L) was obtained with a purity of 96.06%. The EPS was characterized to have only one symmetrical sharp peak by high-performance size-exclusion chromatography and its molecular weight was 5.17 × 10 4 Da. The GC analysis revealed that EPS only consisted of xylose and galactose, and the galactose possessed as high as 98.3% (w/w) of the total monosaccharides. By sulfonation, a sulfated EPS was successfully synthesized with the degree of substitution (DS) of 0.29, which was confirmed using FT-IR spectroscopy. Both EPS and sulfated EPS showed radical scavenging activities, and the antioxidant activities increased after sulfonation. In addition, sulfated EPS was more effective in counteracting the cytotoxicity induced by B . cereus enterotoxins on Caco-2 cells when compared with EPS. In summary, sulfonation is a feasible strategy for improving the biological activities of EPS from L . plantarum ZDY203.